Kosmiese mag in Pseudo-Aristoteles, De mundo , en die Nuwe Testament - Thom, Johan C. (HTS teologiese studies, 2012)
Cosmic power in Pseudo-Aristotle, De mundo, and the New Testament. In order to locate the cosmological views underlying the writings of Paul and other New Testament (NT) authors within their historical contexts it is necessary to compare them with other contemporary worldviews, such as those expressed in philosophical writings of the period. New Testament research has thus far concentrated on the most popular and influential philosophical traditions of NT times, that is, Stoicism and Middle Platonism. Other philosophical traditions may however also offer valuable insights. In this article I suggested that the De mundo attributed to Aristotle but probably dating from the 1st century BCE or CE provides early evidence for a splitting up of the demiurgic function of God in order to preserve God’s transcendence. I furthermore argued that a similar division of divine functions is also evident in some NT texts, for example, John 1, Colossians 1, and Hebrews 1. This notion is explored using Colossians 1 as example.